2023
DOI: 10.1080/2162402x.2023.2210959
|View full text |Cite
|
Sign up to set email alerts
|

M2 macrophage-derived exosomes suppress tumor intrinsic immunogenicity to confer immunotherapy resistance

Abstract: T-cell-based immune checkpoint blockade therapy (ICB) can be undermined by local immunosuppressive M2-like tumor-associated macrophages (TAMs). However, modulating macrophages has proved difficult as the molecular and functional features of M2-TAMs on tumor growth are still uncertain. Here we reported that immunosuppressive M2 macrophages render cancer cells resistant to CD8 + T-cell-dependent tumor-killing refractory ICB efficacy by secreting exosomes. Proteomics and functional studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…TAMs can secrete various cytokines and chemokines, such as epidermal growth factor (EGF), transforming growth factor (TGF), and IL-10 (interleukin-10), which can directly stimulate tumor cell proliferation and facilitate tumor cell migration and invasion, thereby driving tumor growth and dissemination [ 27 , 28 ]. Furthermore, TAMs are among the principal innate immune cell populations in tumors, with M2-TAMs capable of suppressing immune surveillance, aiding tumor cell immune evasion, protecting tumors from cytotoxic immune reactions, and promoting tumor progression [ 29 ]. Additionally, TAMs influence tumor growth by modulating the autophagic process of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…TAMs can secrete various cytokines and chemokines, such as epidermal growth factor (EGF), transforming growth factor (TGF), and IL-10 (interleukin-10), which can directly stimulate tumor cell proliferation and facilitate tumor cell migration and invasion, thereby driving tumor growth and dissemination [ 27 , 28 ]. Furthermore, TAMs are among the principal innate immune cell populations in tumors, with M2-TAMs capable of suppressing immune surveillance, aiding tumor cell immune evasion, protecting tumors from cytotoxic immune reactions, and promoting tumor progression [ 29 ]. Additionally, TAMs influence tumor growth by modulating the autophagic process of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…While tumor-intrinsic YTHDF1, a versatile and powerful m6A reader, was demonstrated to drive immune evasion and resistance to immune checkpoint inhibitors via promoting MHC-I degradation, an exosome-mediated CRISPR/Cas9 system was shown to introduce YTHDF1 deficiency and restore expression of MHC-I and tumor immune surveillance [ 230 ]. Additionally, M2 macrophage-derived exosome was revealed to confer cancer cell resistance to ICT via apolipoprotein E (ApoE)-mediated downregulation of MHC-I [ 231 ]. Upregulated expression of PD-L1 on surface of tumor cells is a common strategy hijacked by various type of cancer to evade immune surveillance [ 232 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…Just as almost all treatments of cancer except for surgery, the accompanying resistance to tumor immunotherapy is an inevitable obstacle to be overcome currently [ 390 , 391 ]. As aforementioned above, many exosomes-based mechanisms underlying evasion of immune surveillance confer to resistance to immunotherapy including ICT [ 206 , 230 , 231 ], and CAR-T therapy in cancer as well [ 247 ]. In addition, reshaped TME resulted from conventional treatment such as radiotherapy, as well as ICT has also been increasingly recognized as key player in development of acquired resistance to cancer immunotherapy [ 392 , 393 ], which adding new dimension to the field of even complicated exosome-mediated mechanisms [ 394 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…Zheng et al. showed that exosomal ApoE from M2‐Exos suppressed the ATPase activity of BiP, resulting in decreased MHC‐I expression, thereby resisting ICBT therapy 91 . Cianciaruso et al.…”
Section: Myeloid Cell‐derived Exosomesmentioning
confidence: 99%
“…90 Zheng et al showed that exosomal ApoE from M2-Exos suppressed the ATPase activity of BiP, resulting in decreased MHC-I expression, thereby resisting ICBT therapy. 91 Cianciaruso et al showed that tumour-associated macrophagederived exosomes (TAM-Exos) and cancer cell-derived exosomes were the main cellular sources of exosomes in a syngeneic MC38 colon cancer model. TAM-Exos isolated with an anti-CSF1R exhibited an M1-like tumourassociated macrophage (TAM) signature and promoted T-cell proliferation even though the TAM cells themselves exhibited an M2-like phenotype.…”
Section: Tumour-associated Macrophage-derived Exosomesmentioning
confidence: 99%